Legal consequences for not referring a question for preliminary ruling - Turičnik, Edita (Pravnik, 2014)
According to decentralized character of the EU legal system, national courts are the ordinary courts in matters of EU law and should as such guarantee effective legal protection of individual's rights deriving from EU law. To ensure uniform application of EU law provisions and especially to prevent possible divergent interpretations, a preliminary ruling procedure was created, found in Article 267 TFEU. On the basis of the mentioned Article national courts may, and sometimes must, refer a question to the CJEU and ask for clarification of the meaning or review of the validity of an act of EU law, which is of relevance to the case upon which national courts need to adjudicate, since the CJEU has an exclusive monopoly of interpretation on questions of EU law. This Paper first shortly examines, when national courts have the right and when the duty to refer question to the CJEU and which are exceptions to this obligation, but the main topic of the paper is focused on the possible legal consequences which may follow, if national courts do not fulfil their obligations under Article 267 TFEU. The author concludes, that those possible remedies are indeed able to strengthen the principles of primacy and effectiveness of EU law; notwithstanding, they should not be considered as an alternative for preliminary ruling proceedings.
Keywords: European Union; Evropska unija; odločanje; pristojnosti; sodišča